Investigation of Macular Choroidal Thickness and Blood Flow Change by Optical Coherence Tomography Angiography After Posterior Scleral Reinforcement - Zhang, Zheng; Qi, Yue; Wei, Wenbin; Jin, Zi-Bing; Wang, Wen; Duan, Anli; Liu, Wu (Frontiers in Medicine, 2021)
Purpose: This work aimed to study the effect of posterior scleral reinforcement (PSR) on choroidal thickness (CT) and blood flow. Methods: This study included 25 eyes of 24 patients with high myopia ( ≤ -6.0 dioptres or axial length ≥ 26.0 mm) who underwent PSR surgery. All patients completed the 1-month follow-up visit. Myopic macular degeneration (MMD) was graded according to the International Meta-Analysis for Pathologic Myopia (META-PM) classification based on color fundus photographs. Swept-source optical coherence tomography angiography (SSOCTA) was performed to investigate CT, choroidal perfusion area (CPA), and choriocapillaris perfusion area (CCPA) change following PSR surgery. Results: The distribution of MMD categories was 9 (36.0%) in category 1, 10 (40.0%) in category 2, and 6 (24.0%) in category 3 or 4. MMD severity was strongly correlated with CT (all P < 0.01) and CPA (all P < 0.04). Postoperative CT at each sector increased significantly at 1 week's follow-up, compared to preoperative measures (all P < 0.05). Postoperative CPA at subfoveal, superior, inferior, and nasal sectors also increased significantly 1 week after PSR surgery (all P < 0.05). Moreover, the increased CT, CPA, and CCPA remain after PSR surgery at 1 month's follow-up, but the difference was not statistically significant. Conclusions: We demonstrated that the CT and choroidal blood flow increased significantly in patients with high myopia who underwent PSR surgery in a short period of time. In addition, the CT and CPA were independently associated with MMD. However, whether the transient improvement of the choroidal circulation could prevent long-term progression of high myopia warrants further study in the future.